ENVIRONMENTAL MODELING AND ANALYSIS FOR IMPACT SIMULATION OF THE BRAZILIAN FOREST CODE IN THE LANDSCAPE STRUCTURE OF DF - Luiz, Carlos Henrique Pires; Steiken, Valdir Adilson (Mercator, 2023)
In this paper, we analyzed the impacts of changes in environmental legislation and the implementation of the Brazilian Forest Code – BFC, on the landscape structure. In order to achieve this, data from the Rural Environmental Registry – RER and vegetation/soil coverage maps were used, in addition to a series of other environmental variables, for the construction, calibration and validation of an environmental model capable of simulating the impacts of changes in the law in the Landscape structure, from the perspective of three distinct scenarios. Scenario 1 considers the recovery of Areas of Permanent Preservation – APP and percentages of Legal Reserves – LR in accordance with the current BFC, maintaining the excess of native vegetation – ENV, which are outside these areas; Scenario 2 considers the application of the current BFC and suppression of all remaining native vegetation – RNV which are not located in protected areas; Scenario 3 considers the full recovery of the APP and LR bands, regardless of the size of the property and maintenance of the ENV. As main results, it was identified that in the Federal District, in relation to APP, the change in law represents a loss of 5,285 ha that will no longer be recovered. Most of this unrecovered area, 53%, is located in properties with more than 15 fiscal modules – the larger properties. The amnesty in relation to LR represents 2,459 ha, mainly due to the exceptions found in article 67 of the BFC.  Keywords : Rural Environmental Registry, Environmental Regularization Program, Simulation.